2020
DOI: 10.1186/s12964-020-00657-z
|View full text |Cite
|
Sign up to set email alerts
|

PIWI-interacting RNAs and PIWI proteins in glioma: molecular pathogenesis and role as biomarkers

Abstract: Glioma is the most common primary brain tumor, and is a major health problem throughout the world. Today, researchers have discovered many risk factors that are associated with the initiation and progression of gliomas. Studies have shown that PIWI-interacting RNAs (piRNAs) and PIWI proteins are involved in tumorigenesis by epigenetic mechanisms. Hence, it seems that piRNAs and PIWI proteins may be potential prognostic, diagnostic or therapeutic biomarkers in the treatment of glioma. Previous studies have demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 86 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…Piwi-interacting RNA (piRNA) was first identified in 2006 and is defined as a small non-coding RNAs that binds specifically to PIWI family proteins in testicular germ cells [ 6 , 7 ]. PiRNA is approximately 30 nucleotides in length and regulates transposon silencing and mRNA turnover, both of which are critical for gametogenesis and germ cell functions [ 8 11 ]. Recent studies have shown that piRNA is effectively expressed in both normal somatic cells and cancer cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Piwi-interacting RNA (piRNA) was first identified in 2006 and is defined as a small non-coding RNAs that binds specifically to PIWI family proteins in testicular germ cells [ 6 , 7 ]. PiRNA is approximately 30 nucleotides in length and regulates transposon silencing and mRNA turnover, both of which are critical for gametogenesis and germ cell functions [ 8 11 ]. Recent studies have shown that piRNA is effectively expressed in both normal somatic cells and cancer cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, piRNA plays an important role in gastric cancer, liver cancer, glioma, and other diseases. Based on these correlations, piRNA is expected to serve as a new target for cancer treatment[ 6 , 10 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…P-element-induced wimpy testis (PIWI)-interacting RNA (piRNA) was first found in the ovarian germ cells of Drosophila melanogaster in 2006. This novel short non-coding small RNA has an average length of 26-31 nucleotides[ 5 ] and functions by binding with PIWI protein to form a piRNA-induced silencing complex (PIRISC)[ 6 - 8 ]. piRNA plays an important role in transposon silencing, epigenetic regulation, protein regulation of genome rearrangement, spermatogenesis, and germ stem cell maintenance[ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no piRNA-based clinical trial, as the study as possible biomarkers has barely begun. Gliomas is the disease in which most progress has been made [ 102 , 187 ].…”
Section: Importance and Future Perspectivesmentioning
confidence: 99%